Il Progetto GRIP: Greenland Ice-core Project. Un programma di perforazione profonda nella calotta glaciale goenlandese organizzato dalla European Science Foundation - Maggi, V (Comitato glaciologico italiano, 1991)
The GRIP project (Greenland Ice-Core Project) which is part of the European Glaciological Programme started in the summer of 1990 and its aim is the drilling of the ice cap where it reaches its maximum thickness. Within 3 years it is to be expected to reach the bedrock at an estimated depth of about 3100 m. In the course of the first year (1990) 770 m have been already drilled. Cores were analyzed "in situ' in an lab excavated within the ice in order to obtain preliminary stratigraphic data by measuring physical and chemical parameters characteristic of the cored ice